Measuring Happiness in Adolescent Samples: A Systematic Review - Justė Lukoševičiūtė; Gita Argustaitė-Zailskienė; Kastytis Šmigelskas (MDPI AG, 2022)
Background: Happiness is a phenomenon that relates to better mental and physical health and even longevity. There has been an increase in surveys assessing subjective well-being as well as happiness, one of the well-being components that reflect one's feelings or moods. Happiness is mostly measured in adult samples. There is a lack of an overview of the tools used to evaluate adolescent happiness, so this paper aimed to review them. Methods: A literature search was performed in the PubMed and PsycArticles databases (2010-2019). In total, 133 papers met the eligibility criteria for this systematic review. Results: The results are grouped according to the type of measure, single or multiple items, that was used in a study. Almost half of the studies (64 of 133) evaluated subjective happiness using single-item measures. The most commonly used scales were the 4-item Subjective Happiness Scale and the Oxford Happiness Questionnaire. Among the 133 articles analyzed, 18 reported some validation procedures related to happiness. However, in the majority of cases (14 studies), happiness was not the central phenomenon of validation, which suggests a lack of happiness validation studies. Conclusions: Finally, recommendations for future research and for the choice of happiness assessment tools are presented.